The Relationship Between ESG Performance and Firm Value Across All Sectors in Asia, Europe, and Australia: A Systematic Literature Review - Mila Failasufa; Inten Mutia; Ika Sasti Ferina (LP2M IAIN Palopo, 2026)
In recent years, the integration of Environmental, Social, and Governance (ESG) principles into business strategies has become crucial due to increasing climate concerns and stakeholder demands. This study aims to systematically review empirical evidence on the relationship between ESG performance and firm value across various sectors in Asia, Europe, and Australia. Using a qualitative Systematic Literature Review (SLR) approach using the PRISMA protocol, 20 high-quality articles from 2020–2025 were analyzed. Data extraction focused on variables, theories, findings, and methodologies. The synthesis revealed a dominant positive correlation between ESG performance and firm value, particularly in Asia and Australia, with significant geographic and sectoral heterogeneity. ESG had a positive impact in the manufacturing and construction sectors, while results in the coal, oil, and aviation sectors were inconclusive or negative. Methodological diversity, including ESG data sources and firm value proxies, influenced the findings. In conclusion, the relationship between ESG and firm value is contextual, requiring ESG research and implementation to be tailored to local and sectoral characteristics.